PENGARUH KEPEMILIKAN, ARUS KAS, DIVIDEN DAN KINERJA TERHADAP KEBIJAKAN HUTANG - Saraswaty, Shieta; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of managerial ownership, institutional ownership, free cash flow, dividend policy, and profitability, and sales growth to the debt policy of property and real estate companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2014 periods. The research method has been done by using purposive sampling method and the samples are 215 financial statements of 45 property and real estate companies and the data has been obtained from the official website of Indonesia Stock Exchange (www.idx.co.id). The test has been done by using multiple linear regressions analysis and SPSS (Statistical Package for Social Sciences) 20 version and the independent variables that have been applied are managerial ownership, institutional ownership, free cash flow, dividend policy, profitability, and sales growth and its influence to the dependent variable i.e. debt policy. The result of multiple analyses shows that managerial ownership, institutional ownership, free cash flow and profitability have significant influence to the debt policy. Meanwhile, dividend policy, and sales growth do not have any influence to the debt policy, and the 0.21 or 21% R square the independent variable influence dependent variable.Keywords: ownership, cash flow, dividend, financial performance, debt policy.